Analgesic Effect Comparison Between Nalbuphine and Sufentanil for Patient-Controlled Intravenous Analgesia After Cesarean Section - Sun, Shen; Guo, Yundong; Wang, Tingting; Huang, Shaoqiang (Frontiers in Pharmacology, 2020)
Background: Efficient maternal pain relief after cesarean delivery remains challenging, but it is important to improve outcomes for the mother and the newborn during the puerperium. We compared the analgesic effect of nalbuphine (a κ receptor agonist/μ receptor antagonistic) with that of sufentanil (a μ-receptor agonist) in patient-controlled intravenous analgesia (PCIA) after cesarean section. Methods: We enrolled 84 patients scheduled for elective cesarean sections with spinal anesthesia and randomized them into either nalbuphine or sufentanil groups (42 patients each). Pain scores, PCIA drug consumptions, degree of satisfaction, and adverse events were recorded as outcome measures. Results: The pain scores at rest and uterine cramping pain scores in the nalbuphine group were lower than those in the sufentanil group at 6, 12, and 24 hours after the operation. Also, the pain scores while switching to a seated position were lower in the nalbuphine group than in the sufentanil group at 6 and 12 hours after the operation (P<0.05). We found no significant differences in the PCIA drug consumption between the two groups. The degree of satisfaction in patients in the nalbuphine group was higher than that of patients in the sufentanil group (P=0.01). Adverse events did not differ in the two groups. Conclusion: PCIA with nalbuphine provides better analgesia and higher patient satisfaction than sufentanil after cesarean section.